Microbial impact of Canada geese (Branta canadensis) and whistling swans (Cygnus columbianus columbianus) on aquatic ecosystems. - Hussong, D (1979)
Quantitative and qualitative analyses of the intestinal bacterial flora of Canada geese and whistling swans were carried out with the finding that wild birds harbor significantly more fecal coliforms than fecal streptococci. The reverse was typical of captive and fasting birds. Neither Salmonella spp. nor Shigella spp. were isolated from 44 migratory waterfowl that were wintering in the Chesapeake Bay region. Enteropathogenic Escherichia coli were detected in seven birds. Geese eliminated 10(7) and swans 10(9) fecal coliforms per day. Results of in situ studies showed that large flocks of waterfowl can cause elevated fecal coliform densities in the water column. From the data obtained in this study, it is possible to predict the microbial impact of migratory waterfowl upon aquatic roosting sites.